PENGARUH NILAI WAKTU PADA BIAYA OPERASIONAL KENDARAAN (BOK) MOBIL PENUMPANG DALAM PEMILIHAN RUTE JALAN EKSISTING DAN JALAN LINGKAR AMBARAWA - Iqbal Caesariawan; Devisanti Nabilah Rizky; Ismiyati Ismiyati; Epf. Eko Yulipriyono (Jurnal Karya Teknik Sipil, 2015)
Nowadays as the mobility of a person develop tends to require a shorter time, where time is a commodity that can’t be saved or stored so that time is very important to everyone. In this case the time value changes according to the level of income. When faced with two choices of Ring Road and Existing Road Ambarawa, person with high income levels tend to more appreciate the value of time by choose a route that has a value of time much more efficient. The aim of this study is to analyze the effect of the time value of road users traveling in the magnitude of Vehicle Operating Costs (VOC) for route selection on the Ring Road and Ambarawa Existing Road with Logit Binomial Model. The methodology of this research is to analyze the value of travel time Income Approach method is used, then to analyze the results of the calculation of the Vehicle Operating Costs (VOC) formula used PCI (Pacific Consultant International), and then to analyze the route selection with Logit Binomial Model. Results of the analysis can be concluded that the greater the time value of road users, then the probability of route selection-A also increased, due to the time value of road users with greater income, more important than the time value of road users with lower incomes.